Do Axé À Aleluia: transformações do campo religioso cachoeirano (1980-2007) - Silva, Lizandra Santana da (2014)
This dissertation examines the conversion and religious transit of worshipers of Candomblé and the Nossa Senhora da Boa Morte Brotherhood to protestant denominations in Cachoeira -Ba, between 1980 and 2007. We investigated the prevalence of women in conversions by analyzing the main reasons why they decided to seek another religious affiliation, as well as the reasons for men's adherence to Protestant groups. We recognized that women's motivations were related to marital and/or family issues, while for men they referred to personal matters. We analyzed the demonization of Candomblé by evangelical groups, especially the Igreja Universal do Reino de Deus as well as the speech of practitioner of Candomblé before the disqualification practices of Candomblé and the numerical growth of conversions practitioner of Candomblé to the Protestant denominations. The applicant was disqualified and demonization of african-Brazilian religious practices. Observe how new religious affiliation and religious transit influence on family relationships, analyzing how conflict and family tensions began to be administered by the newly converted. It was recurrent the disqualification and demonization of african-Brazilian religious practices. We observe how his new religious affiliation and religious transit had influenced family relationships, analyzing how conflict and family tensions began to be administered by the newly converted.